1992
DOI: 10.1093/infdis/166.4.792
|View full text |Cite
|
Sign up to set email alerts
|

Enteropathogens Associated with Acute and Persistent Diarrhea in BangladeshiChildren <5 Years of Age

Abstract: A longitudinal study of diarrhea was carried out from May 1988 to April 1989 by household surveillance of 705 children less than 5 years old in rural Bangladesh. Stool samples were examined for enteric pathogens at the beginning of each diarrheal episode. For persistent episodes, stool examination was repeated on days 15-17 of the illness. For each case of persistent diarrhea, stool samples from age-matched acute diarrheal and healthy controls were examined. Compared with healthy controls, cases of diarrhea we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
116
4
6

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(130 citation statements)
references
References 21 publications
4
116
4
6
Order By: Relevance
“…Their role in diarrheal disease, however, has been controversial (11,18,25). Several groups have used age-dependent susceptibility to explain epidemiological discrepancies, since a positive association with diarrhea was found when study populations were age-stratified (1,18,20,35,47).Clinical microbiologists have to hesitate to classify the DAEC isolates as causative agents. DAEC probably comprise a heterogeneous group of organisms with variable enteropathogenicity (45).…”
mentioning
confidence: 99%
“…Their role in diarrheal disease, however, has been controversial (11,18,25). Several groups have used age-dependent susceptibility to explain epidemiological discrepancies, since a positive association with diarrhea was found when study populations were age-stratified (1,18,20,35,47).Clinical microbiologists have to hesitate to classify the DAEC isolates as causative agents. DAEC probably comprise a heterogeneous group of organisms with variable enteropathogenicity (45).…”
mentioning
confidence: 99%
“…Diffusely adherent Escherichia coli has recently been accepted as a diarrheagenic strain of E. coli that causes watery diarrhea in young children (1)(2)(3). Diffusely adherent E. coli shares a characteristic pattern of infection of epithelial cells in which the bacteria form a diffuse pattern around the host cells and is accompanied by an elongation of the microvilli (4).…”
mentioning
confidence: 99%
“…Some of the authors 14,21 showed an association of bacterial pathogens with rotavirus positive cases. Various enteropathogens isolated in their study 25,26 . The PAGE system used in this study was very simple to perform and the results were available on the same day.…”
Section: Resultsmentioning
confidence: 99%